Applied population biology - Jain, S. K. (Sudhanshu Kumar), 1926-; Botsford, Louis W. (Dordrecht : Springer Netherlands, 1992)
An increasing variety of biological problems involving resource management, conservation and environmental quality have been dealt with using the principles of population biology (defined to include population dynamics, genetics and certain aspects of community ecology). There appears to be a mixed record of successes and failures and almost no critical synthesis or reviews that have attempted to discuss the reasons and ways in which population biology, with its remarkable theoretical as well as experimental advances, could find more useful application in agriculture, forestry, fishery, medicine and resource and environmental management. This book provides examples of state-of-the-art applications by a distinguished group of researchers in several fields. The diversity of topics richly illustrates the scientific and economic breadth of their discussions as well as epistemological and comparative analyses by the authors and editors. Several principles and common themes are emphasized and both strengths and potential sources of uncertainty in applications are discussed. This volume will hopefully stimulate new interdisciplinary avenues of problem-solving research.
Population biology and its application to practical problems -- The biology of land restoration -- Genetic conservation in captive populations and endangered species -- Population biology and conservation of rare plants -- Genetics of weed invasions -- Population management in new plant breeding approaches -- The population dynamics and control of the parasitic nematode Trichostrogylus tennis in red grouse in the North of England -- Population biology of helminth infections of veterinary importance and its relevance to control -- Ecological theory and biological control -- Habitat fragmentation, species diversity, extinction, and design of nature reserves -- Perspectives on adaptive policy design in fisheries management -- Applying the principles of population biology: assessment and recommendations.
Elektronická reprodukce.
Keywords: populační biologie; aplikovaná ekologie; druhová rozmanitost; biodiverzita; population biology; applied ecology; species diversity; biodiversity; e-knihy online; e-books online